SAAVEDRA AND MODERN IUS GENTIUM - Rivera García, Antonio (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
The author in this article tackles firstly the question of diplomacy and regulation of war and peace with Saavedra Fajardo’s main work as his starting point. Secondly, he examines the principle of modern Ius gentium as it appears in the work of the baroque author.
Keywords: Diplomacy; war; peace; aversion; interest; balance; neutrality; hegemony; decadence